Carbon dioxide exchange in Norway spruce at the shoot, tree and ecosystem scale - Wallin, Göran; Linder, Sune; Lindroth, Anders; Räntfors, Mats; Flemberg, Sara; Grelle, Achim (Tree Physiology, 2001)
Net CO 2 exchange in a 35-year-old boreal Norway spruce ( Picea abies (L.) Karst.) forest in northern Sweden was measured at the shoot (NSE), tree (NTE) and ecosystem levels (NEE) by means of shoot cuvettes, whole-tree chambers and the eddy covariance technique, respectively. We compared the dynamics of gross primary production (GPP) at the three levels during the course of a single week. The diurnal dynamics of GPP at each level were estimated by subtracting half-hourly or hourly model-estimated values of total respiration (excluding light-dependent respiration) from net CO 2 exchange. The relationship between temperature and total respiration at each level was derived from nighttime measurements of NSE, NTE and NEE over the course of 1 month. There was a strong linear relationship ( r 2 = 0.93) between the hourly estimates of GPP at the shoot and tree levels, but the correlation between shoot- and ecosystem-level GPP was weaker ( r 2 = 0.69). However, the correlation between shoot- and ecosystem-level GPP was improved ( r 2 = 0.88) if eddy covariance measurements were restricted to periods when friction velocity was ≥ 0.5 m s−1. Daily means were less dependent on friction velocity, giving an r 2 value of 0.94 between shoot- and ecosystem-level GPP. The correlation between shoot and tree levels also increased when daily means were compared ( r 2 = 0.98). Most of the measured variation in carbon exchange rate among the shoot, tree and ecosystem levels was the result of periodic low coupling between vegetation and the atmosphere at the ecosystem level. The results validate the use of measurements at the shoot and tree level for analyzing the contribution of different compartments to net ecosystem CO 2 exchange.